Feng-Liao-Chang-Wei-Kang Combined with 5-Fluorouracil Synergistically Suppresses Colitis-Associated Colorectal Cancer via the IL-6/STAT3 Signalling Pathway. (5th October 2020) - Zhong, Lifan; Yang, Fan; Gan, Lianfang; Yang, Zhaoxin; Tian, Shuhong; Huang, Mianqing; Lv, Chuanzhu; Huang, Ling
Abstract : Background . Colitis-associated colorectal cancer (CAC) develops from active colonic inflammation, which is characterized by the production of proinflammatory cytokines that can induce mutations. IL-6 is produced by multiple cell types located within the tumor microenvironment including tumor-infiltrating immune cells, stromal cells, and the tumor cells themselves. The aim of our study was to explore the mechanism of Feng-Liao-Chang-Wei-Kang (FLCWK) and 5-fluorouracil (5-FU) in treating CAC. Method . HCT116 cells were treated with 5-FU in the absence or presence of FLCWK. Cell proliferation was assayed by MTT assays. Apoptosis and the cell cycle phases were detected by flow cytometry. Western blotting and Q-PCR assays were used to detect the expression levels of proteins and genes related to the IL-6/STAT3 signalling pathway. A mouse model for CAC was established by treating animals with 12.5 mg/kg azoxymethane (AOM) followed by 3 cycles of 2.5% dextran sodium sulphate (DSS). The associated pathological changes were determined after haematoxylin and eosin (H&E) staining. The expression of related proteins and genes in various tissues was examined using immunofluorescence techniques. Results . FLCWK enhanced the ability of 5-FU to promote apoptosis by inhibiting the proliferation of HCT116 cells and blocking the IL-6/STAT3 pathway. FLCWK combined with 5-FU reduced the number and size of colon tumors in mice with CAC and significantly increased their survival rate. In the CAC model, FLCWK synergized with 5-FU to inhibit the phosphorylation of STAT3, preventing IL-6/STAT3 signal transduction and thus further inducing apoptosis and inhibition of colon cancer cell proliferation. Conclusion . FLCWK can inhibit the activation of STAT3 by reducing the production of IL-6, thereby increasing the occurrence of colitis-related colorectal cancer with 5-FU.